A Critical Perspective on Ageism and Modernization Theory - De Tavernier, Wouter (Social Inclusion, 2019)
Modernization theory has often been used to explain country differences in levels of ageism. The commentary at hand questions its usefulness in the analysis of ageism today for two reasons. First, modernization theory was developed to discuss social status of older people, not ageism. Second, social policies and management practices that emerged with industrialization are being rolled back over the last decades. We therefore argue for the reconsideration of the relationship between modernization and ageism and to re-assess it in order to better explain country differences in ageism in the 21st century.